Model updating of uncertain parameters of carbon/epoxy composite plates from experimental modal data. (1st September 2019) - Cuadrado, M.; Artero-Guerrero, J.A.; Pernas-Sánchez, J.; Varas, D.
Abstract: This work presents a methodology to obtain physically-sound models of composite structure laminates using a combination of modal analysis, numerical modelling and parameter updating, avoiding the common uncertainties on the constructions of similar numerical models. Moreover this model establishes the baseline (pristine situation) of the dynamic behaviour of the set of composite plates. Therefore it could be applied for condition assessment or quality manufacturing control of existing structures through a non-destructive Structural Health Monitoring (SHM), and hence it could help to detect degradation or defects of the composite components. The driven data of the methodology were the modal frequencies and shapes of composite plates. To obtain these values an extensive experimental campaign of modal analysis has been performed on a set of carbon/epoxy laminates. A multiple input single output technique has been applied, using a roving hammer exciting the plates at evenly distributed Degrees of Freedom (DoF), and a mono-axial accelerometer attached to a single DoF reference point. The use of a high dense grid of points has allowed to identify a number of natural frequencies greater than usual in similar works, as well as improving the smoothness of the mode shape. Modal characteristics numerically obtained from a Finite Element Method (FEM) model based on manufacturer reference data were compared with experimental results. This baseline model was updated through a gradient based optimization algorithm. Before the process of model updating, a sensitivity analysis has been performed to identify the driven uncertain parameters using a Montecarlo approach. This technique reduces the number of parameters to be optimized to a small set increasing the efficiency of the methodology. As a result of the whole process, a physically more accurate model is obtained on which discrepancies with the corresponding experimentally measured modal parameters are drastically reduced. Analysis of the consistency of the adjusted numerical parameters has been done with alternative experimental tests (Quasi Static Loading (QSL) and Ultrasonic inspection).